Brave new world : and Brave new world revisited - Huxley, Aldous, 1894-1963.; Huxley, Aldous, 1894-1963. (New York : HarperPerennial Modern Classics, 2005)
Bernard Marx becomes a citizen in an utopian World-State where babies are born in laboratories, there is no violence, all citizens take drugs for depression, and contentment overrides the free will of the populace, and presents the social climate in 1958, and the threats against personal freedoms that seemed to be precursers to the novel's empty civilization.
Brave new world -- Brave new world revisited.
Adult
Keywords: Collectivism -- Literary collections; Genetic engineering -- Literary collections; Passivity (Psychology) -- Literary collections; Totalitarianism -- Literary collections; Collectivism -- Literary collections; Genetic engineering -- Literary collections; Passivity (Psychology) -- Literary collections; Totalitarianism -- Literary collections